Jurnal Skripsi ANALISIS KESALAHAN BERBAHASA DALAM AKUN INSTAGRAM UMN AL-WASHLIYAH (KAJIAN SEMANTIK) TAHUN AKADEMIK 2024-2025: Analisis kesalahan berbahasa kajian semantik - Nur Ainun Br Lubis; Nirmawan Nirmawan (Universitas Asahan, 2025)
Short story writing is a critical skill in Indonesian language learning, as it fosters students’ imagination, critical thinking, and self-expression. However, many students still struggle with this skill due to limited motivation and the lack of engaging instructional media. This study aims to examine the effectiveness of using the Wattpad application to improve students’ short story writing skills in Grade XI Social Science at Madrasah Aliyah Al Washliyah Tebing Tinggi. Employing a quantitative approach, the study adopted a quasi-experimental design with a pretest-posttest control group. Sixty students were selected and assigned to two groups: the experimental group used Wattpad as a writing platform, while the control group was taught using conventional methods. A short story writing test was used as the research instrument, assessed across six dimensions: narrative structure, plot, character development, setting, language style, and originality. Data were analyzed using an independent t-test. The results revealed a statistically significant difference in posttest scores between the two groups, with the experimental group showing greater improvement, particularly in the dimensions of language style and originality. These findings indicate that Wattpad is effective in enhancing students’ writing performance by offering a creative, interactive, and motivating learning environment. The study recommends integrating digital storytelling platforms such as Wattpad into language instruction to foster student literacy and creativity in the digital era.